Cultural Hybridization in The Lego Ninjago Movie: A Third Space Analysis Through Homi Bhabha’s Theory (EUFONI: Journal of Language, Literary, and Cultural Studies, 2025)
This study examines The LEGO Ninjago Movie as a cultural text that embodies the principles of cultural hybridization in a globalized media landscape. Grounded in Homi Bhabha’s theory of the Third Space, the analysis highlights how the film blends traditional East Asian motifs with Western narrative conventions to construct a hybrid cultural identity. By focusing on the characters of Lloyd and Garmadon, the film presents a nuanced exploration of the tension between individual identity formation and the constraints of inherited cultural roles. The narrative and visual elements create a metaphorical space where diverse cultural elements intersect, critique, and transform one another. In doing so, The LEGO Ninjago Movie not only bridges cultural divides but also contributes to ongoing conversations about transnational identity, cultural negotiation, and the role of popular media as a site for intercultural dialogue and mutual understanding.